Genetic Variants in Transcription Factors Are Associated With the Pharmacokinetics and Pharmacodynamics of Metformin. Issue 3 (22nd May 2014) - Goswami, S; Yee, S W; Stocker, S; Mosley, J D; Kubo, M; Castro, R; Mefford, J A; Wen, C; Liang, X; Witte, J; Brett, C; Maeda, S; et al.
<x xml:space="preserve">Abstract</x> One‐third of type 2 diabetes patients do not respond to metformin. Genetic variants in metformin transporters have been extensively studied as a likely contributor to this high failure rate. Here, we investigate, for the first time, the effect of genetic variants in transcription factors on metformin pharmacokinetics (PK) and response. Overall, 546 patients and healthy volunteers contributed their genome‐wide, pharmacokinetic (235 subjects), and HbA1c data (440 patients) for this analysis. Five variants in specificity protein 1 (SP1), a transcription factor that modulates the expression of metformin transporters, were associated with changes in treatment HbA1c (P < 0.01) and metformin secretory clearance (P < 0.05). Population pharmacokinetic modeling further confirmed a 24% reduction in apparent clearance in homozygous carriers of one such variant, rs784888. Genetic variants in other transcription factors, peroxisome proliferator–activated receptor‐α and hepatocyte nuclear factor 4‐α, were significantly associated with HbA1c change only. Overall, our study highlights the importance of genetic variants in transcription factors as modulators of metformin PK and response. Clinical Pharmacology & Therapeutics (2014); 96 3, 370–379. advance online publication 25 June 2014. doi:10.1038/clpt.2014.109